Study of ceramic pigments based on Dy2Sn2-xVxO7 - Šulcová, Petra; Fukalová, Pavla; Válek, Lukáš; Trojan, Miroslav (Univerzita Pardubice, 2009)
New high-stability yellow ceramic pigments based on pyrochlore solid solutions Dy2Sn2-xVxO7 were developed employing conventional solid-state reaction synthesis. The synthesis of these colourants involved high-temperature calcination of starting oxides and optimum conditions for their synthesis were determined. The pigments were evaluated from the standpoint of their structure, colour and ability to colour ceramic glazes.